2005
DOI: 10.1021/es048577u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorophyllin-Chitosan on Excretion of Dioxins in a Healthy Man

Abstract: We investigated the usefulness of chitosan and chlorophyllin-chitosan (chl-chitosan) administration for reduction of the body burden of environmental dioxins, including polychlorinated dibenzo-p-dioxins/dibenzofurans (PCDDs/ Fs) and coplanar polychlorinated biphenyls (Co-PCBs), by examining the excretion levels in the feces and sebum of a healthy man. The volunteer ate the same three meals every day during the 40-d experiment, which was composed of five phases (I-V) of 8 d each. In phase I (days 1-8), the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…One human study administering copper chlorophyllin with chitosan (2:1, w/w) observed 49% excretion of the dioxin consumed, a value almost double to the excretion of dioxin when consumed with chitosan alone. [ 79 ] Native chlorophyll can also increase fecal dioxin excretion in a dose‐dependent manner, as shown in rats when incorporated at 0.01–0.5% of the diet. [ 80 ] Dioxin excretion in animals consuming an experimental diet containing 0.2% chlorophyll was ≈34% higher than those consuming a control diet.…”
Section: Bioactivity Of Metallo‐chlorophyll Derivativesmentioning
confidence: 99%
“…One human study administering copper chlorophyllin with chitosan (2:1, w/w) observed 49% excretion of the dioxin consumed, a value almost double to the excretion of dioxin when consumed with chitosan alone. [ 79 ] Native chlorophyll can also increase fecal dioxin excretion in a dose‐dependent manner, as shown in rats when incorporated at 0.01–0.5% of the diet. [ 80 ] Dioxin excretion in animals consuming an experimental diet containing 0.2% chlorophyll was ≈34% higher than those consuming a control diet.…”
Section: Bioactivity Of Metallo‐chlorophyll Derivativesmentioning
confidence: 99%
“…The amount of Trp-P-2-DNA adducts in liver and other organs was significantly decreased in a mice fed with Trp-P-2 and CHL-chitosan [50,51], which was attributed to diminished absorption of CHL-chitosan bound mutagen from the gastrointestinal tract. CHL-chitosan was proven to be beneficial in humans, promoting the excretion of dioxins in feces and sebum [52]. [53].…”
Section: Adsorption Of Hcas On Insoluble Carriersmentioning
confidence: 99%
“…Studies suggest that intake of dietary supplements with either soluble or insoluble fiber can result in decreased accumulation of environmental lipophilic toxins and chemicals in the body tissues and on other hand enhance the excretion of these toxins [34]. Considering these evidences, studies on chitosan, a dietary fiber mainly of marine origin, also provided positive correlation in fecal excretion of fats and environmental toxins like Bisphenol-A [35], Dioxins [36], [37], [38], Phthalates [35] and PCB [38].…”
Section: Dietary Fibrementioning
confidence: 99%
“…A study was designed by Noriyuki Kohuda [36][37][38] on intake of chitosan and fecal excretion of Dioxins in rats. The studied was done using eighteen 4-weeks old Sprague dawley rats for twenty days.…”
Section: Dioxinsmentioning
confidence: 99%